Profile of inflammatory bowel disease nurses in Brazil - de BARROS, Jaqueline Ribeiro [UNESP] (2023)
Background – Nurses play a fundamental role within the inflammatory bowel disease (IBD) multidisciplinary team. Objective – To identify the profile of IBD nurses in Brazil and their work process organization and characterize the health services where they work. Methods – A questionnaire-based research was developed. The inclu-sion criteria were nurses with experience in IBD care, nurses with sci-entific research published in an indexed journal or in process, nurses with master’s or doctorate degrees concluded or in progress, and edu-cator nurses with expertise in IBD. Results – Seventy-four nurses were included, among whom 66 (89.19%) were women; their mean age was 40.63±9.98 years. Sixty-six percent work in the Southeast region, and more than half (54.05%) had a specialization course. Only four (5.41%) nurses worked exclusively with patients with IBD. The main areas of activity were outpatient clinics (39%) and ostomy care (35%). Nursing care was based on the nursing process (51.35%), and the main topics approached in nursing appointment were treatment adherence (72.97%), and ostomy (68.92%). Forty-seven (63.51%) nurses had knowledge on immunosuppressive medications and 52 (70.27%) on biological therapy. Most health services were integrated with a hospital that has clinical (72.97%) and surgical hospitalization units (67.57%), and 46 (62.16%) of them had an infusion center. Conclusion – Describing the work process of IBD nurses can supplement their organization of the IBD assistance process, as they do not follow any specific consensus. In addition, the characteristics necessary for IBD care are not found in all health services.